Assessment of photovoltaic distributed generation – Issues of grid connected systems through the consumer side applied to a case study of Brazil - Camilo, Henrique Fernandes; Udaeta, Miguel Edgar Morales; Veiga Gimenes, André Luiz; Grimoni, Jose Aquiles Baesso (Renewable & sustainable energy reviews, 2017)
The growing application of renewable energy with accessible price and technology, together with Distributed Generation techniques came to bring a paradigm shift in the existing relations of distribution network in the past years. This work assesses the application of Distributed Generation by the consumer as a microgenerator – a “pro-sumer” - by usage of Photovoltaic generation. The presented methodology considers the financial and technical effects in the relations between the utility and the prosumer. The results shows that, even with the residential consumer providing the project and the installation of the PV generation, it is in the distribution framework that this relation is technical and commercially affected, as both the utility and residential microgenerators face the infeasibility of the project. The methodology is validated by an application showing that further regulating and market efforts are required in order to effectively disseminate cogeneration for residential consumers and explore their solar potential.